2020
DOI: 10.3390/ijerph17093204
|View full text |Cite
|
Sign up to set email alerts
|

Organ Trafficking and Migration: A Bibliometric Analysis of an Untold Story

Abstract: The debate over trafficking of human beings for the purpose of organ removal (THBOR) remains largely absent from policy debates, as its crime is hardly detected, reported and sparsely researched. However, criminal networks continue to exploit vulnerable populations, particularly migrants. To help bridge this gap in knowledge, we employ a bibliometric analysis to examine whether the nexus between organ removal and migration is being addressed by the current academic literature. Our results indicate that (1) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Actually, search results in WoS are not presented by author, year, subject and document types like Scopus, but also by institutions and countries [ 32 ], which is convenient for scholars to analyze the distribution of the research organizations. Moreover, WoSCC has been used as a data source in some previous bibliometric studies [ 33 , 34 , 35 , 36 , 37 , 38 ], which further proves its feasibility especially in the natural science domains. The study design was shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 92%
“…Actually, search results in WoS are not presented by author, year, subject and document types like Scopus, but also by institutions and countries [ 32 ], which is convenient for scholars to analyze the distribution of the research organizations. Moreover, WoSCC has been used as a data source in some previous bibliometric studies [ 33 , 34 , 35 , 36 , 37 , 38 ], which further proves its feasibility especially in the natural science domains. The study design was shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 92%
“…On a theoretical level, a great deal has been written about trust and organ donation. 24,[28][29][30] Perverse financial incentives, perceptions of economic gain, reports of transplant practices favouring the wealthy, manipulation of transplant systems in favour of certain patients and unethical procurement practices have all directly diminished public trust in organ transplantation.…”
Section: Transparency and Trustmentioning
confidence: 99%
“…To elaborate: the gift of life or donating life is a pervasive trope within the transplant community, largely due to the National Organ Transplant Act prohibiting the buying or selling or organs within the USA (National Organ Transplant Act, 1984). While an international organ black market is very much active (Gonzalez et al, 2020), financially uncompensated, or altruistic, donation still comprises the vast majority of transplant operations in the USA. But, as we know, this characterisation is limited given that there are dozens if not hundreds of businesses whose financial solvency relies on the continuous circulation of organs.…”
Section: Health and Valuementioning
confidence: 99%